Target costing: review of empirical studies in the automotive sector - Mendes, H. (2015)
This aim of this study is to compare the existing theory on the subject of targetcosting with practices reportedby empirical studies already performed in the automotive sector. We canidentify the following specific purpose: to analyze whether the characteristics of target costing,identified by the theory, are in line with what was reported by the empirical studies already performed in the automotive sector.Data collection was executed usinga review of empirical studies regardingthis topic in automotivecompanies. The data collected allowus to conclude that none of the companiessurveyed reports the use of thetarget costing model with the six characteristicsthe theory associates with it: price leads to cost, customer focus, product design focus, multidisciplinary teams;focus on the costs incurred during the product’slifecycle; involvement of the entire value chain.